Balfour Beatty Rail: Market Entry Strategy for Indonesia, Thailand, and Vietnam - Chang, Hui-Chun; Charoenvisal, Mingmit; Wijaya, Jessica Fidelia (2012)
The aim of this project is to provide Balfour Beatty Rail (BBR) with recommendations of the most efficient market entry mode to enter Indonesia, Thailand, and Vietnam. Our approach has been to offer analysis of these three markets in terms of the country characteristics, industry players, and project opportunities. Our report begins with reviewing literatures on internationalisation and market entry modes. These literatures are then applied to look into International Readiness of BBR, the countries analysis, industry analysis, project opportunities, as well as to recommend strategic action plans. International Readiness chapter provides overview of BBR’s internal aspect and analysis on the type of entry modes available. Country analysis chapter gives an in-depth coverage of the host countries in terms of its distance with the home country, and industry analysis chapter goes one level down to analyse the industry barriers and opportunities and key players. Project analysis chapter discusses about the current and future opportunities in the market. The outcomes of analysis from these four chapters are used to offer recommendations for BBR in the three target countries. Recommendations in the form of strategic action plans are suggested based on BBR’s key success factors and the strategy to choose entry mode as below:  In Indonesia, short-term suggestion is to enter via strategic alliances with key players such as Mitsui/Mitsubishi for the Construction sector, Japan Transportation Consultant/Nippon Koei for the Consultant sector, Invensys/Alstom for the Systems sector, and also with private coal miners. Forming joint venture with local company is worth considering in the long-term when BBR already have substantial business presence in the country.  In Thailand, systems sector is the most favourable sector for BBR to enter; where forming partnership with Bombardier is recommended due to its capabilities in signalling and rolling stock. In construction sector, the short-term suggestion is to be subcontractor of main players i.e. Ch. Karnchang and Italian-Thai, while in the long-term BBR can form a joint venture with a suitable company. In the consulting sector it is recommended to let PB take the lead as to avoid conflict of interest.  In Vietnam, the short-term strategy is to enhance industrial network to establish market presence, and in the long-term it is recommended to form joint venture with local companies as well as target high-speed rail project and project based on PPP scheme.